Comparison of PCR Assay to Culture for Surveillance Detection of Vancomycin-Resistant Enterococci - Paule, Suzanne M. (American Society for Microbiology, 2003)
Direct multiplex PCR assay using vanA and vanB primers, which provides rapid results, was more sensitive than culture on selective media for samples collected by rectal swab (20 of 46 versus 8 of 46; P < 0.001) or perianal swab (17 of 58 versus 12 of 58; P = 0.059) for the detection of gastrointestinal colonization by vancomycin-resistant enterococci.